A review on Deep eutectic solvents as the emerging class of green solvents for membrane fabrication and separations - Yousef Elhamarnah (17869382) (2024)
Deep Eutectic Solvents (DES) are emerging as environmentally friendly and effective alternatives in membrane technology, offering a sustainable edge over traditional solvents. This review compiles the latest advancements in the incorporation of DES into polymeric membrane systems for diverse separation processes, including ultrafiltration (UF), microfiltration (MF), nanofiltration (NF), reverse osmosis (RO), forward osmosis (FO), pervaporation, and membrane distillation (MD). Special attention is devoted to preparation methods involving DES in Non-Solvent Induced Phase Separation (NIPS), Interfacial Polymerization (IP), and electrospinning. Notable developments include the integration of DES into various membrane types, such as Thin-Film Composite (TFC) in NF and FO, Supported Liquid Membranes (SLMs) in pervaporation, and asymmetric mixed matrix membranes in UF. The review introduces a classification of DES as either hydrophilic or hydrophobic, revealing their respective roles and applications. A critical examination of hydrogen bond donors (HBD) and acceptors (HBA) offers insights into the separation mechanisms behind DES-based membranes. A central challenge addressed is the complex behavior of DES leaching within membranes, which has varying implications on the performance, efficiency, and purity of filtration processes. While some studies have shed light on the stability and intentional leaching of DES components to enhance membrane functionality, research is notably sparse when it comes to the specific issue of DES leaching in water filtration processes. This highlights an existing research void and suggests a direction for future studies. This comprehensive review serves as a roadmap for the further development and wider industrial adoption of DES-based membrane technologies while identifying both strengths and areas for improvement. Other Information Published in: Journal of Molecular Liquids License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.molliq.2024.124250